Occupational Asthma Occurrence Analysis and Factor Factors Affecting on Furniture Workers in Balongrejo Village Kecamatan Berbek Nganjuk - Fitra Handika Hutama (Journal for Quality in Public Health, 2019)
Wood working or furniture workers are workers at risk of exposure to dust, whether derived from sawmill assembly or wooden welding, thus at risk of developing occupational diseases such as respiratory diseases such as asthma. Lack of self-discipline workers to use self-protection tool (APD) in the form, mask is one of the factors that influence the incidence of respiratory diseases with the main symptoms of cough. This happens because the workers inhale sawdust or wooden dust. This study is an obeservational study with cross sectional design. Samples and respondents are furniture workers in Balongrejo village, Berbek sub-district, Nganjuk regency, as many as 120 people taken by cluster random sampling of 94 people. The statistic test used is logistic regression. The result of statistical test shows that significant value <0.05 means H1 is accepted and H0 is rejected. This means that there is an influence between smoking, the use of personal protective equipment (masks), and the temperature of the workspace against occupational asthma events, and a significant value> of 0.05 means that H1 is rejected and H0 accepted This means no effect on the occurrence of occupational asthma, of influencing factors above the most dominant factor affecting the occurrence of occupational asthma in furniture workers is smoking and the use of personal protective equipment (masks). Efforts that can be done in overcoming this problem is the active role of Disnakertrans of Nganjuk Regency to make the order regulation to the owner of Furniture Trade Enterprise to provide PPE to the workers, the active role of health officer in giving health counseling for the furniture workers.